MIG and the regulatory cytokines IL-10 and TGF-β1 correlate with malaria vaccine immunogenicity and efficacy. - Susanna J Dunachie; Tamara Berthoud; Sheila M Keating; Adrian V S Hill; Helen A Fletcher (PLoS ONE, 2010)
Malaria remains one of the world's greatest killers and a vaccine is urgently required. There are no established correlates of protection against malaria either for natural immunity to the disease or for immunity conferred by candidate malaria vaccines. The RTS,S/AS02A vaccine offers significant partial efficacy against malaria.mRNA expression of five key cytokines interferon-gamma (IFN-γ), monokine induced by gamma (MIG), interleukin-10 (IL-10), transforming growth factor-β (TGF-β) and forkhead box P3 (FoxP3) in peripheral blood mononuclear cells were measured by real-time RT-PCR before and after vaccination with RTS,S/AS02A and Modified Vaccinia virus Ankara encoding the circumsporozoite protein (MVA-CS) in healthy malaria-naïve adult volunteers. The only significant change was in IFN-γ mRNA expression, which was increased seven days after vaccination (P  =  0.04). Expression of MIG mRNA seven days after vaccination correlated inversely with time to detection of parasites by blood film in an experimental sporozoite challenge (r = 0.94 P  =  0.005). An inverse relationship was seen between both TGF-β1 and IL-10 mRNA at baseline and the anti-circumsporozoite IgG antibody response (r  =  -0.644 P  =  0.022 and r =  -0.554 P = 0.031 respectively). This study demonstrates the potential for MIG expression as a correlate of protection against malaria. Baseline levels of the regulatory cytokines TGF-β and IL-10 inversely correlated with antibody levels post vaccination and warrant further studies to improve understanding of individual differences in response to vaccination.